2020
DOI: 10.1002/jbmr.3987
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Disrupt Skeletal Angiogenesis Through Transrepression of NF-κB–Mediated Preosteoclast Pdgfb Transcription in Young Mice

Abstract: In the growing skeleton, angiogenesis is intimately coupled with osteogenesis. Chronic, high doses of glucocorticoids (GCs) are associated with decreased bone vasculature and induce osteoporosis and growth failure. The mechanism of GC‐suppression of angiogenesis and relationship to osteoporosis and growth retardation remains largely unknown. Type H vessels, which are regulated by preosteoclast (POC) platelet‐derived growth factor–BB (PDGF‐BB), are specifically coupled with bone formation and development. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 61 publications
(161 reference statements)
1
15
0
Order By: Relevance
“…It has long been recognized that exogenous GCs have divergent effects on osteoclasts both in vivo and in vitro due to differences in strain, age, glucocorticoid dose, or experimental set-up 93 . Our finding that MPS treatment decreases osteoclast numbers in femoral metaphysis in growing young mice is consistent with previous work conducted using the same age of young mice 74,75 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It has long been recognized that exogenous GCs have divergent effects on osteoclasts both in vivo and in vitro due to differences in strain, age, glucocorticoid dose, or experimental set-up 93 . Our finding that MPS treatment decreases osteoclast numbers in femoral metaphysis in growing young mice is consistent with previous work conducted using the same age of young mice 74,75 .…”
Section: Discussionsupporting
confidence: 93%
“…Metaphyseal vascular cells and osteoprogenitors undergo senescence in response to GC treatment. It is well-recognized that angiogenesis coupled with osteogenesis is abundant in the metaphysis of the growing skeleton in mice but declines in young adult mice, in which bone growth slows 71,[73][74][75] . Therefore, it is logical to postulate that highly proliferative vascular cells and osteoprogenitor cells in metaphysis are particularly vulnerable to GC treatment.…”
Section: Resultsmentioning
confidence: 99%
“… 26 , 27 A recent study showed that NF-ĸB can bind to the Pdgfb promoter in preosteoclasts and is necessary for the induction of PDGF-BB expression. 28 Interestingly, Siglec-G negatively regulated the activation of NF-ĸB. It is unknown whether Siglec-15 has a similar effect to that of Siglec-G in regulating the signals of NF-ĸB.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, exogenous glucocorticoid administration is the principal iatrogenic cause for secondary osteoporosis and nontraumatic osteonecrosis of the femoral head (ONFH), which adds a tremendous economic burden to individuals and healthcare systems [ 1 , 2 ]. In patients with glucocorticoid-induced bone loss, angiogenesis is suppressed, accompanied by circulatory impairment, persistent bone destruction, increased apoptosis of osteocytes, disrupted balance of mesenchymal stem cells’ (MSCs) differentiation, fat embolism, and intramedullary pressure changes [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%